Cramp‐fasciculation syndrome in patients with and without neural autoantibodies. Issue 3 (17th December 2013) - Liewluck, Teerin; Klein, Christopher J.; Jones, Lyell K.
ABSTRACT Introduction: We investigated the clinical, electrophysiological and neural autoantibody characteristics in cramp‐fasciculation syndrome (CFS) patients. Methods: We reviewed Mayo Clinic records from 2000 to 2011 to identify clinically defined CFS patients who underwent neural autoantibody testing. Stored sera of patients who tested positive for antibodies to voltage‐gated potassium channel complex (VGKC complex) were analyzed further for leucine‐rich glioma‐inactivated 1 (LGI1) or contactin‐associated protein‐2 immunoglobulin G (CASPR2‐IgG) antibodies. Results: Thirty‐seven patients were identified. Twelve were seropositive for neural autoantibodies. Clinical manifestations were similar in seropositive and seronegative patients, although central and autonomic neuronal hyperexcitability symptoms were more common in seropositive cases. No patients had a malignancy. Repetitive tibial nerve stimulation at 10 Hz revealed longer afterdischarges in seropositive patients. Two of 7 patients with VGKC‐complex autoimmunity demonstrated LGI1 or CASPR2‐IgG antibodies. Only 2 of 12 seropositive patients required immunotherapy. Conclusions: VGKC‐complex autoimmunity occurs in a minority of CFS patients. Antibody positivity was associated with extramuscular manifestations, typically without malignancy. Target antigens within the VGKC complex remain unknown in most patients. Muscle Nerve49:351–356, 2014